2016
DOI: 10.1007/s00395-016-0576-z
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2 signaling at the crossing between heart failure and cancer

Abstract: The dual role of ErbB2 (or HER-2) in tumor growth and in physiological adaptive reactions of the heart positions ErbB2 at the intersection between cancer and chronic heart failure. Accordingly, ErbB2-targeted inhibitory therapy of cancer may lead to ventricular dysfunction, and activation of ErbB2 for heart failure therapy may induce malignancy. The molecular processes leading to the activation of ErbB2 in tumors and cardiac cells are, however, fundamentally different from each other. Thus, it must be feasible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 58 publications
2
52
0
1
Order By: Relevance
“…Activation of NRG/ErbB signaling in mammalian models of cardiac remodeling resulted in an improved left ventricular structure and function with a concomitant reduction in CM apoptosis, increased angiogenesis, and reduced cardiac fibrosis (Vermeulen et al, 2016). These positive results formed the basis for several clinical trials.…”
Section: Wnt Signalingmentioning
confidence: 92%
See 1 more Smart Citation
“…Activation of NRG/ErbB signaling in mammalian models of cardiac remodeling resulted in an improved left ventricular structure and function with a concomitant reduction in CM apoptosis, increased angiogenesis, and reduced cardiac fibrosis (Vermeulen et al, 2016). These positive results formed the basis for several clinical trials.…”
Section: Wnt Signalingmentioning
confidence: 92%
“…Neuregulin-1 (NRG-1) is a member of the neuregulin growth factor family and is the isoform most present in the heart, where the tyrosine kinase receptors ErbB4 and-to a lesser extent-ErbB3 serve as its receptors (Rupert and Coulombe, 2015). Upon binding, ErbB receptors can form a heterodimer with ErbB2 and activate cardioprotective signaling pathways (Vermeulen et al, 2016). The importance of the ErbB2 protein in cardiac physiology was highlighted in studies in which cardiotoxicity was reported in patients with breast cancer treated with trastuzumab, a recombinant monoclonal antibody directed against ErbB2.…”
Section: Wnt Signalingmentioning
confidence: 99%
“…A second challenge is the potential for increased cancer risk due to cell cycle activation in non-CMs. For example, both NRG1 and Yap signals have oncogenic potentials and are known to be involved in cancers 178, 179 . Precise targeting of mitogenic stimuli to CMs is necessary to minimize oncogenic risk.…”
Section: Regulation Of CM Proliferationmentioning
confidence: 99%
“…Studies have shown that lack of HER2 in mouse heart causes dilated cardiac chambers and myocardial wall thinning and as a result development of cardiomyopathy [3,4]. HER2 signaling is essential in vital cardiomyocyte functions and prevention of cardiac dysfunction [5,6]. Trastuzumab-induced cardiotoxicity indicated by a decrease in left ventricular ejection fraction (LVEF) or congestive heart failure [7,8], and a high risk of death among cancer patients [8].…”
Section: Introductionmentioning
confidence: 99%